185k views
4 votes
Complete the square to transform the expression x2 + 4x + 2 into the form a(x − h)2 + k.

User Chelofm
by
4.9k points

2 Answers

6 votes

Answer:

(x + 2)2 − 2

Step-by-step explanation:

Just took the test and got it right

User Mireya
by
5.2k points
0 votes

Answer:

Explanation:

y = (x^2 + 4x) + 2

Take 1/2 of the linear term 4/2 = 2 and square that result. 2^2 = 4.

Put it after 4x

y = (x^2 + 4x + 4) +2 Subtract what you put inside the brackets on the outside.

y = (x^2 + 4x + 4) + 2 - 4 Combine the right.

y = (x^2 + 4x + 4) - 2 Express the brackets as a square.

y = (x + 2)^2 - 2

That's your answer

a = 1

h = 2

k = -2

User Icecrime
by
4.9k points